Institutional Diversity in the Planning Process Yields Similar Outcomes for Vegetation in Ecological Restoration. Issue 8 (2nd August 2020) - Heneghan, Liam; Westphal, Lynne M.; Ross, Kristen A.; Watkins, Cristy; Gobster, Paul H.; Iannone, Basil V.; Tudor, Madeleine; Vining, Joanne; Wali, Alaka; Zellner, Moira; Wise, David H.
Abstract: Conservation organizations undertaking ecological restoration and the lands they manage constitute a social-ecological system (SES). We implemented SES analysis to examine the relationship between diversity in organizational structure and restoration planning processes, and vegetation outcomes on the ground. Understanding the restoration consequences of multiple approaches to planning and implementation is relevant to assessing the resilience of this SES, especially if disagreements about the effectiveness of some approaches lead to conflict in the socio-political arena. We studied 10 conservation organizations in the Chicago Wilderness region that are restoring Midwestern oak woodlands of global conservation concern. Despite the institutional diversity of these organizations, we found little relationship between restoration planning and vegetation outcomes. This result has implications for the resilience of restoration as an SES, since similar outcomes from diverse processes should increase resilience of this SES, especially when controversial restoration practices are employed, and when priorities and funding levels change.